Adaptation of the Core CDIO Standards 3.0 to STEM Higher Education - A. I. Chuchalin (Высшее образование в России)
It is proposed to adapt the new version of the internationally recognized standards for engineering education the Core CDIO Standards 3.0 to the programs of basic higher education in the field of technology, natural and applied sciences, as well as mathematics and computer science in the context of the evolution of STEM. The adaptation of the CDIO standards to STEM higher education creates incentives and contributes to the systematic training of specialists of different professions for coordinated teamwork in the development of high-tech products, as well as in the provision of comprehensive STEM services. Optional CDIO Standards are analyzed, which can be used selectively in STEM higher education. Adaptation of the CDIO-FCDI-FFCD triad to undergraduate, graduate and postgraduate studies in the field of science, technology, engineering and mathematics is considered as a mean for improving the system of three-cycle STEM higher education.